2017
DOI: 10.1002/adsc.201700276
|View full text |Cite
|
Sign up to set email alerts
|

Chlorotrimethylsilane and Sodium Iodide: A Useful Combination for the Regioselective Deoxygenation of Arylalkyl‐α‐Diketones

Abstract: An efficient regioselective deoxygenation of arylalkyl-diketones by the couple trimethylsilylchloride/sodium iodide has been reported. In all cases, the deoxygenation takes place on the carbonyl group (C=O) proximal to the aromatic ring in methylene chloride at room temperature in good yields, furnishing a series of variously functionalized alkylbenzylketones. A large range of functional groups were well tolerated on the ortho-, meta-and para-positions by this mild process regardless of their electronic ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

5
2

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…d) Yield of 40% when using 5 equiv of TMSCl/NaI. Moreover, as we previously observed with arylalkyl-α-diketones, [9] the presence of electron-rich substituent(s) on aromatic ring(s) is not necessary for the reduction process to occur (entries 1 and 2). In entries 3-10, we were pleased to observe that the presence of electron-withdrawing groups (EWGs) as Cl, F, Br, CF3 on ortho, meta and para-positions did not affect the yield of the desulfurization process and the corresponding diarylmethanes 7b-h were obtained with excellent yields.…”
Section: Resultsmentioning
confidence: 65%
See 1 more Smart Citation
“…d) Yield of 40% when using 5 equiv of TMSCl/NaI. Moreover, as we previously observed with arylalkyl-α-diketones, [9] the presence of electron-rich substituent(s) on aromatic ring(s) is not necessary for the reduction process to occur (entries 1 and 2). In entries 3-10, we were pleased to observe that the presence of electron-withdrawing groups (EWGs) as Cl, F, Br, CF3 on ortho, meta and para-positions did not affect the yield of the desulfurization process and the corresponding diarylmethanes 7b-h were obtained with excellent yields.…”
Section: Resultsmentioning
confidence: 65%
“…[8] This reducible system having a great functional group tolerance in CH2Cl2 (on the contrary to TMSI), was also extended to selectively reduce various arylalkyl-α-diketones into alkylbenzylketones with high yields. [9] Herein, we wish to report the reductive properties of the TMSCl/NaI in CH2Cl2 towards a variety of dithioketals, which were successfully desulfurized in good yields (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…In this context, we believe that an alternative milder process is still needed using for example inexpensive and soft reagents to achieve this transformation at room temperature in the presence of various functional groups. Recently, we reported the interesting reducing properties of the TMSCl/NaI association in CH 2 Cl 2 towards various functional groups as unsymmetrical α-diketones, [15] α-keto esters, [16] and hydrazones [16] derivatives. Under similar reaction conditions, we next demonstrated that a variety of dithioacetals were cleanly such as hydrazones, N-tosylhydrazones, and ketimines reacted well under these conditions to give the expected ketones in high yields.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we reported the interesting reducing properties of the TMSCl/NaI association in CH 2 Cl 2 towards various functional groups as unsymmetrical -diketones, [15] -ketoesters, [16] and hydrazones [16] derivatives. Under similar reaction conditions, we next demonstrated that a variety of dithioacetals were cleanly desulfurized at rt [17] in CH 2 Cl 2 using this metal-free process in a Mozingo-type reaction.…”
Section: Introductionmentioning
confidence: 99%